Risk factors for postpartum urinary incontinence - Lígia da Silva Leroy; Adélia Lúcio; Maria Helena Baena de Moraes Lopes (SciELO, 2016)
Abstract OBJECTIVE: To investigate the risk factors for postpartum urinary incontinence (UI) and its characteristics. METHOD: This was a case-control study with 344 puerperal women (77 cases and 267 controls) with up to 90 days postpartum. In a single session, participants were given a questionnaire with sociodemographic and clinical data and two others that assessed urine leakage, leakage situations, and type of UI. RESULTS: Stress UI was present in 45.5% of the women, incidents of urine leakage several times a day in 44.2%, of which 71.4% were in small amounts and 57.1% when coughing or sneezing. In 70.1% of cases, UI began during pregnancy and remained through the postpartum period. After running a binary logistic regression model, the following factors remained in the final model: UI during pregnancy (OR 12.82, CI 95% 6.94 - 23.81, p<0.0001), multiparity (OR 2.26, CI 95% 1.22 - 4.19, p=0.009), gestational age at birth greater or equal to 37 weeks (OR 2.52, CI 95% 1.16 - 5.46, p=0.02) and constipation (OR 1.94, CI 95% 1.05 - 5.46, p=0.035). CONCLUSION: Most often, UI first appeared during pregnancy and remained through the postpartum period. Urinary incontinence during pregnancy, multiparity, gestational age at birth greater or equal to 37 weeks, and constipation were presented as risk factors. In the studied group, stress UI was more frequent.